Vedolizumab is associated with changes in innate rather than adaptive immunity in patients with inflammatory bowel disease. Issue 1 (5th May 2018) - Zeissig, Sebastian; Rosati, Elisa; Dowds, C Marie; Aden, Konrad; Bethge, Johannes; Schulte, Berenice; Pan, Wei Hung; Mishra, Neha; Zuhayra, Maaz; Marx, Marlies; Paulsen, Maren; Strigli, Anne; et al.
Abstract : Objective: Vedolizumab, a monoclonal antibody directed against the integrin heterodimer α4β7, is approved for the treatment of Crohn's disease and ulcerative colitis. The efficacy of vedolizumab has been suggested to result from inhibition of intestinal T cell trafficking although human data to support this conclusion are scarce. We therefore performed a comprehensive analysis of vedolizumab-induced alterations in mucosal and systemic immunity in patients with inflammatory bowel disease (IBD), using anti-inflammatory therapy with the TNFα antibody infliximab as control. Design: Immunophenotyping, immunohistochemistry, T cell receptor profiling and RNA sequencing were performed using blood and colonic biopsies from patients with IBD before and during treatment with vedolizumab (n=18) or, as control, the anti-TNFα antibody infliximab (n=20). Leucocyte trafficking in vivo was assessed using single photon emission computed tomography and endomicroscopy. Results: Vedolizumab was not associated with alterations in the abundance or phenotype of lamina propria T cells and did not affect the mucosal T cell repertoire or leucocyte trafficking in vivo. Surprisingly, however, α4β7 antibody treatment was associated with substantial effects on innate immunity including changes in macrophage populations and pronounced alterations in the expression of molecules involved in microbial sensing, chemoattraction and regulation of the innate effector response. These effects were specific to vedolizumab, not observed in response to the TNFα antibody infliximab, and associated with inhibition of intestinal inflammation. Conclusion: Our findings suggest that modulation of innate immunity contributes to the therapeutic efficacy of vedolizumab in IBD. Trial registration number: NCT02694588